ANALISA PRESSURE BEJANA TEKANAN SESUAI STANDARD ASME - M. Saragih, Andreas (JURNAL ILMIAH TEKNIK SIPIL, 2024)
A pressure vessel is a device for storing pressurized fluid or a Pressure Vessel is a vessel other than a steam engine in which there is pressure that exceeds the external air pressure, used to accommodate gas or gas mixtures including air either compressed to become liquid or in a dissolved or frozen state. The pressure in the pressure vessel must be known how much the maximum pressure can enter and the pressure vessel is able to withstand this pressure. Using ASME as a standard can be done in calculations or data processing.